W poszukiwaniu twardego jądra ewolucjonizmu - Jodkowski, Kazimierz (Filozofia Nauki, 2001)
The author of the paper distinguishes so-called «soft» theories, which adapt to many empirical situations, even mutually contradictory ones, and «hard» theories, which exclude many imaginable empirical situations (i.e. results of observations and/or experiments). Every theory is soft to some degree, due to possible modifications of the protective belt of auxiliary hypotheses and redefinition of scientific terms. According to Popper’s or Lakatos’ criteria, absolutely «soft» theory is unfalsifiable and therefore unscientific. The «harder» is a given theory, the better. The author presents the results of his search for «hard» elements of evolutionary theory and concludes that it seems that this theory has no empirical hard core.